UnityMol prototype for FAIR sharing of molecular‐visualization experiences: from pictures in the cloud to collaborative virtual reality exploration in immersive 3D environments. Issue 6 (28th May 2021) - Martinez, Xavier; Baaden, Marc
Abstract : Visualization renders structural molecular data accessible to a broad audience. An approach to share molecular‐visualization experiences based on FAIR principles is described. The workflow is exemplified with recent COVID‐19‐related data. Abstract : Motivated by the current COVID‐19 pandemic, which has spurred a substantial flow of structural data, the use of molecular‐visualization experiences to make these data sets accessible to a broad audience is described. Using a variety of technology vectors related to the cloud, 3D and virtual reality gear, how to share curated visualizations of structural biology, modeling and/or bioinformatics data sets for interactive and collaborative exploration is examined. FAIR is discussed as an overarching principle for sharing such visualizations. Four initial example scenes related to recent COVID‐19 structural data are provided, together with a ready‐to‐use (and share) implementation in the UnityMol software.